The Influence of Digital Promotion, Product Quality and Brand Image on Purchasing Decisions Which Impact on Consumer Satisfaction of Ventela Shoes at the Haii Shoes Store, Kendal: The Influence of Digital Promotion, Product Quality and Brand Image on Purchasing Decisions Which Impact on Consumer Satisfaction of Ventela Shoes at the Haii Shoes Store, Kendal - Dwi Aryanti, Ega Aprilya; Prabowo, Heri; Dharmaputra, M Fadjar (INTERNATIONAL CONFERENCE OF ECONOMICS AND BUSINESS, 2025)
This study aims to identify factors influencing purchasing decisions and consumer satisfaction at Haii Shoes Store, Kendal. The factors examined include digital promotion, product quality, and brand image. The analysis method used is Partial Least Squares (PLS) to test convergent validity, discriminant validity, and path analysis. The results show that the independent variables (digital promotion, product quality, and brand image) collectively explain about 67% of the variability in purchasing decisions (R-square = 0.67) and 76% of the variability in consumer satisfaction (R-square = 0.76). Effect size analysis (f square) indicates that each independent variable has a significant effect on the dependent variables. Prediction relevance (Q square) for purchasing decisions is 0.35 and for consumer satisfaction is 0.42, indicating a good predictive capability of the model.